2009
DOI: 10.1021/bi900281s
|View full text |Cite
|
Sign up to set email alerts
|

Functional Energetic Landscape in the Allosteric Regulation of Muscle Pyruvate Kinase. 3. Mechanism

Abstract: Mammalian pyruvate kinase exists in four isoforms with characteristics tuned to specific metabolic requirements of different tissues. All of the isoforms, except the muscle isoform, exhibit typical allosteric behavior. The case of the muscle isoform is a conundrum. It is inhibited by an allosteric inhibitor, Phe, yet it has traditionally not been considered as an allosteric enzyme. In this series of study, an energetic landscape of rabbit muscle pyruvate kinase (RMPK) was established. The phenomenon of inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…These conclusions are further strengthened by our fluorescence data and model simulations described in two following papers of this issue (36, 37). …”
Section: Discussionsupporting
confidence: 68%
“…These conclusions are further strengthened by our fluorescence data and model simulations described in two following papers of this issue (36, 37). …”
Section: Discussionsupporting
confidence: 68%
“…At 23 °C the resulting free energy change for the R→T transition can be estimated to be ~ 3.4 kcal/(mol of tetramer), decreasing to zero at 38 °C, which is close to a rabbit body temperature (3638). Significance of this finding is discussed in the next paper (30). …”
Section: Resultsmentioning
confidence: 75%
“…2. Visual inspection of the figure indicates that the fluorescence quantum yield of the R-state is lower than that of the T-state as evident by a gradual increase of I PEP / I 0 at low temperatures and a sharp decrease above 30°C where the fraction of the unliganded T-state is known to significantly increase (1, 4, 30). Due to the preferential affinity of PEP for the R-state, the presence of PEP shifts the enzyme population toward the R-state resulting in a decrease of fluorescent intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies of rabbit skeletal muscle have shown that pyruvate kinase, a critical enzyme for the flow of substrate into oxidative phosphorylation, is highly temperature sensitive. [14][15][16] Its activity is greatest around 35°C-38°C and drops off rapidly as the temperature rises due to conformational changes. If the rise in muscle temperature during exercise compromises the activity of pyruvate kinase, then the flow of the substrate into the Krebs cycle and, therefore, the rate of production of ATP will be reduced.…”
Section: Heller and Grahnmentioning
confidence: 99%